A descriptive analysis of Anglicisms in ecuadorian magazines - Cedeño Albán, Ana Cecilia (2011)
The theme of this investigation was to analyze Anglicisms usages in Ecuadorian Magazines. This research was about the phenomenon of Anglicisms found in Ecuadorian magazines that contains a deep linguistic analysis of the most common Anglicisms found in magazines from Santo Domingo, and Quito Ecuador under the following categories cultural, scholarly and general interest; such as Vision, Hogar, La Casa, América Economía, and Criterios . In order to develop this descriptive investigation the qualitative and quantitative methods were used. Qualitative investigation is defined as research that analyzes data in written documents. The qualitative method was used for the linguistic descriptions of Anglicisms. Quantitative investigation is defined as the process of measurement. With this method, comparisons were made among variables to determine which variable contains the highest number of Anglicisms and which are the 10 most commonly used Anglicisms in each variable. This research concludes that the influence w£of Anglicisms in Ecuadorian magazines mostly appears in technological and economical magazines and that many of them benefit Spanish but others are not necessary.